The Role of Customization, Security, and Flexibility in Enhancing Trust and Continuance Intentions of Digital Payment Services: Insights from Pakistan - Bashir, Roshan; Sheikh, Muhammad Ramzan; Arshad, Tabassum; Asghar, Neelum (iRASD Journal of Economics, 2023)
Nowadays e-banking via different platforms of bank is very common in European countries. In Pakistan, the intention of digital transactions services is very useful and common nowadays. However, some people’s intention is that the transactions through mobile services is not trusted for that reason the adoption of digital transactions services is still in the initial stage. This study is based on the diffusion of the invention theory and inculcate the experiences of intention to use digital transactions services by a trust-facilitating role. The data is collected through the survey method from ordinary end users who are making the digital transactions via Jazz Cash and Easy paisa within a Pakistan and the current study’s aim is to give guide lines to the administrators of digital transactions service providers to strengthen the customization, security features, flexibility, and which wins the trust of customers.